E-Waste Recycling and Why It Is Important - Ghazali, Ihwan; Sakundarini, Novita (Bincang Sains dan Teknologi, 2024)
The exponential growth of electronic waste (e-waste) has become a pressing concern. This alarming trend is expected to persist. The study identifies falling prices as a primary driver behind the surge in e-waste, making electronic devices more affordable and accessible globally. Developing countries, particularly in Asia, bear a significant share of this burden, as a burgeoning middle class with disposable incomes contributes to increased purchases and frequent replacements of electronic goods. Asia alone accounts for more than 40 percent of the global e-waste generated. The critical need for urgent and coordinated global efforts to address the escalating challenge of e-waste. It highlights the environmental hazards posed by improper disposal and the socio-economic impact on developing regions. As electronic consumption continues to rise, effective strategies must be implemented to mitigate the adverse effects of e-waste, emphasizing sustainable practices, responsible manufacturing, and international collaboration.